2009
DOI: 10.4049/jimmunol.0803600
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Mammalian Target of Rapamycin Controls the Loss of TCRζ in Lupus T Cells through HRES-1/Rab4-Regulated Lysosomal Degradation

Abstract: Persistent mitochondrial hyperpolarization (MHP) and enhanced calcium fluxing underlie aberrant T cell activation and death pathway selection in systemic lupus erythematosus. Treatment with rapamycin, which effectively controls disease activity, normalizes CD3/CD28-induced calcium fluxing but fails to influence MHP, suggesting that altered calcium fluxing is downstream or independent of mitochondrial dysfunction. In this article, we show that activity of the mammalian target of rapamycin (mTOR), which is a sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
297
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 230 publications
(313 citation statements)
references
References 78 publications
(131 reference statements)
14
297
0
2
Order By: Relevance
“…It was reported that mTOR kinase activities of T cells are increased in SLE patients compared with matched healthy controls (6). Such enhanced mTOR activities could be reversed by rapamycin treatment (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that mTOR kinase activities of T cells are increased in SLE patients compared with matched healthy controls (6). Such enhanced mTOR activities could be reversed by rapamycin treatment (6).…”
mentioning
confidence: 99%
“…Such enhanced mTOR activities could be reversed by rapamycin treatment (6). Suppression of mTOR activity with rapamycin treatment can markedly prolong survival, decrease anti-dsDNA Ab production, and ameliorate nephritis activity in MRL/lpr lupus-prone mice (7).…”
mentioning
confidence: 99%
“…Another pathway for activation of mTOR in lupus T cells is from depletion of glutathione, which regulates the elevation of mitochondrial transmembrane potential or mitochondrial hyperpolarization (23). N-acetyl cysteine (NAC), which is an antioxidant and a precursor of GSH, inhibits mTOR and significantly improves disease activity and reduces anti-dsDNA in lupus patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…An increase in Akt activation has been demonstrated in the peripheral blood from SLE patients, concurrently with an up-regulation of the phosphorylation of one of its downstream targets, GSK3 [95], known as a negative regulator of cell cycle progression [96]. An abnormal activation of mTOR has been demonstrated in human SLE [97], and promising results in the treatment of the disease have been obtained with rapamycin, which could act by facilitating the differentiation of Treg cells and promoting the expansion of other subsets able to limit the T cell stimulation of auto-reactive B cells [98]. Beyond Akt and mTOR, a dysregulation in leptin expression has also been found in SLE patients [99; 100], but further studies are required to unlock the mechanisms that control its secretion.…”
Section: Dysregulation Of Metabolism During Autoimmunitymentioning
confidence: 99%